ONLINE PICTURE-GUIDED WORKSHEET TO IMPROVE THE FIRST CONDITIONAL SENTENCE WRITING: A CLASSROOM ACTION RESEARCH (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
This study aims to find out whether or not an online picture-guided worksheet can improve the ability of vocational high school (VHS) students in writing the first conditional sentences significantly. This study follows the use of a grammar system in writing sentences as one of the micro-skills in writing (Brown, 2007). The data show that VHS students have problems in terms of the grammatical rules, or lexical items, or in both of the aspects. The online picture-guided worksheet is chosen as a way to help VHS students in composing the sentences based on the first conditional rules during the pandemic era. Pictures can stimulate students’ creativity in finding ideas about what to write. Online worksheet makes the works accessible in terms of time and place for the students. This study is conducted in two cycles to eleventh graders in one of the public vocational high schools in Semarang. The finding shows that the students have various ideas in writing the first conditional sentences based on the provided pictures. In addition, there is an improvement in students’ writing ability for first conditional sentences. Hopefully, this study will give insight into the teaching of conditional sentences.